A New Paradigm for Outpatient Diagnosis and Treatment of Lower Urinary Tract Symptoms Utilizing a Mobile App/Software Platform and Remote and In-Office Visits: A Feasibility Study. Issue 1 (28th January 2021) - Li, Eric S. W.; Poon, Michael W.; Manyevitch, Roni; Thomas, Devon N.; Blaivas, Jerry G.
Abstract: Introduction: This pilot/feasibility study evaluated a new diagnostic and treatment paradigm for patients with lower urinary tract symptoms using a software platform comprised of a mobile app, validated patient reported outcome questionnaires, bladder diaries and remote patient monitoring. Methods: New urology referrals for lower urinary tract symptoms completed validated lower urinary tract symptoms questionnaires and 24-hour bladder diaries on a mobile app. Patients were triaged based on symptom severity into an urgent or routine office visit or a remote visit. Outcome metrics assessed include acceptability, practicality, implementation and integration. Results: Of 500 urology consults there were 226 (45%) patients with new lower urinary tract symptoms referrals of whom 201 (89%) had email addresses. In all there were 182 men and 19 women, aged 18 to 87 years (mean 59, SD 17), of whom 71/201 (35%) registered, 57/71 (80%) completed the app and 41/57 (72%) elected remote visits. Mean time from urology referral to initiation of a remote or in-office diagnostic and treatment plan was 7.4 days (SD 5.9) and 7.7 days (SD 7.6), respectively. Conclusions: Of patients who completed the app 72% were triaged to a remote visit. Time from urology referral to initiation of remote or in-office diagnostic and treatment plan averaged 1 week. This paradigm for management of lower urinary tract symptoms has potential to optimize the clinical workflow, improve health care outcomes and reduce costs.